Availability, Quality, and Implementability of Canadian Clinical Practice Guidelines for Female Sexual Dysfunction. (1st August 2022) - Tomalty, D; Giovannetti, O; Sa, V; Adams, M
ABSTRACT: Introduction: Sexual health problems are common among Canadian women, though they often go unaddressed and untreated in clinical settings. Clinical practice guidelines (CPGs) are systematically developed statements that facilitate structured, evidence-based guidance for specific clinical circumstances. Their potential benefits to patients and practitioners are dependent upon comprehensive guideline development processes that consolidate best available evidence, and guide successful implementation into practice. Little is known about the curation, availability, quality, and implementability of Canadian CPGs for women's sexual health problems and female sexual dysfunction (FSD). Objective: i) To determine the availability of protocols guiding the curation of Canadian CPGs ii) To assess the availability, quality, and implementability of Canadian CPGs for women's sexual health concerns and FSD. Methods: A systematic search for publicly available documents referencing Canadian CPG development processes was conducted. Websites associated with provincial and national health bodies, in addition to relevant professional medical organizations, and electronic databases PubMed and Google Scholar were searched. A separate search was conducted to retrieve Canadian CPGs specific to women's sexual health and FSD using similar methodology. FSD CPGs that met the criteria of including recommendations on FSD screening, management, and resources went on to subsequent analyses using the AGREE-II and AGREE-REX tools to assess CPG quality and implementability, respectively, and qualitative content analysis to identify the scope and thematic content of the CPGs. Results: Two national guidelines for Canadian CPG development were identified. 3/13 Canadian provinces and territories had protocols outlining processes for general CPG development. National and provincial documents varied in their recommended methodologies for CPG curation and updating evidence suggesting a lack of standardization. Two Canadian CPGs specific to FSD and sexual concerns were identified: one from the Canadian Urological Association, and one from the Society of Obstetrics and Gynecology of Canada (SOGC). Only the SOGC guideline contained information regarding screening, management, and resources for FSD, and thus underwent subsequent analysis. The SOGC guideline scored highly with respect to the domains of Scope and Purpose (79%), and Clarity of Presentation (86%), though it did not sufficiently address the remaining AGREE-II domains, scoring lowest in Applicability (44%) and Editorial Independence (13%). AGREE-REX scoring was 58%, suggesting it was moderately implementable. Qualitative analysis revealed a focus on the importance of healthcare providers ensuring they have the necessary skills and knowledge to assess and manage sexual health problems, though the details of these skills and knowledge were not consistently defined. Conclusions: There is a lack of standardization of the process of CPG curation in Canada and limited Canadian CPGs guiding best practices for screening and management of FSDs, and provision of additional resources. This study highlights the strengths and deficiencies in the current Canadian CPGs for FSD. Canadian CPG developers should consider FSD a topic of priority and continue to make attempts to curate comprehensive, evidence-based CPGs in this field that are implementable in all local Canadian contexts. The ISSWSH Process of Care for the Identification of Sexual Concerns and Problems in Women may serve as a valuable resource in improving Canadian-specific FSD CPGs. Disclosure: No